Histopathologic Type: An Independent Prognostic Factor in Primary Soft Tissue Sarcoma of the Extremity? - KOEA, Jonathan B. (Institutional Knowledge at Singapore Management University, 2003)
We attempted to define the effect of tumor histotype on local recurrence, distant metastasis, and disease-specific survival in patients with surgically treated primary extremity sarcoma. Methods: A total of 951 patients with primary, localized soft tissue extremity sarcoma were followed up prospectively. Patient- and tumor-related variables, including histopathologic type, were used to identify independent prognostic factors for the study end points of local recurrence, distant recurrence, and disease-specific survival. Results: There were 137 local recurrences, and significant adverse prognostic factors for local recurrence were patient age >50 years, microscopically positive margins, and malignant peripheral nerve tumor. Adverse prognostic factors for distant recurrence (200 patients) were tumor size >5 cm, tumors beneath the investing fascia, high tumor grade, and leiomyosarcoma. Of the 199 patients who died of disease-related causes, patient age >50 years, tumors beneath the investing fascia, high tumor grade, microscopically positive margin, tumor size >5 cm, leiomyosarcoma, and malignant peripheral nerve tumor were adverse prognostic factors. Conclusions: These data suggest that differences in biological behavior may exist between sarcoma histotypes and deserve further study.